Labour's First Year : 1945-46 (London : Common Wealth Publications Committee, 1946)
1946 1946 1940s 27 pages INTERNATIONAL AFFAIRS Their Promise We have in "Let Us Face the Future" the Labour Party's programme for the 1945 General Election. In the section on International Affairs headed "A World of Progress and Peace," we read : "We must consolidate in peace the great war-time association with the U.S.A. and the U.S.S.R. Let it not be forgotten that in the years leading up to the war the Tories were so scared of Russia that they missed the chance to establish a partnership which might very well have prevented the war." Further we read : "We should build a new United Nations, allies in a new war on human ignorance and want... The British Labour Movement comes to the task of international organisation with one great asset ; it has a common bond with the working people of all countries." Foreign Minister Bevin For the all-important job of Foreign Minister, vital at the end of the second World War with which capitalism has cursed the earth, the Labour Party selected Ernest Bevin. He took over the Foreign Office in July, 1945, at the time of the Potsdam Conference. The War in the East had not ceased ; the bond of a common enemy united the Big Three Powers still. This Conference set up a Council of Foreign Ministers — of the Three, China and France — to consider the Peace Treaties. It was announced that the Allies sought to extirpate militarism and Nazism in Germany while, however : "The German people be given the opportunity to prepare for the eventual reconstruction of their life on a democratic and peaceful basis." It was resolved, too, that the reparation claims of the U.S.S.R. would be met (in part) by removals from the Russian zone in Germany while Britain would get reparations from Germany's Western Zone. This should be stressed, as the British Press has talked far more of Russian appropriation of plant than of the discreet visits of British businessmen to Germany to list machinery for transfer to Britain. A true Socialist policy would have opposed 4 15X/2/98/21